EVALUATION OF CONCURRENT MALARIA AND DENGUE CO-INFECTIONS AMONG FEBRILE PATIENTS VISITING A TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL OBSERVATIONAL STUDY - KUMAR, Binay Kumar Mahto; Sanjay Kumar; Sant Kumar (Student’s Journal of Health Research Africa, 2024)
Background Malaria and dengue are mosquito-borne diseases found in Bihar, West Bengal, Uttar Pradesh, Punjab, Haryana, Delhi, Gujarat, Kerala, Karnataka, and Tamil Nadu. High mortality and morbidity rates make these diseases a major public health issue in these places. The underreporting and misdiagnosis of dengue and malaria concomitant infection is common. Aim and Objective To assess the incidence of co-infections with dengue and malaria and to evaluate and compare the severity of these co-infections with that of mono-infections of either disease, based on clinical and laboratory parameters. Material and Method A cross-sectional observational study was conducted involving patients who presented with fever and symptoms indicative of malaria and/or dengue. A total of 497 serum samples were collected from these clinically suspected cases. All samples were tested for dengue NS1 antigen and IgM/IgG antibodies using ELISA and immunochromatographic (ICT) tests. Diagnosis of malaria was confirmed via rapid malaria antigen test kits and the identification of Plasmodium spp. through peripheral blood smear microscopy (both thick and thin films). Results Among the febrile patients, 155 (31.19%) tested positive for dengue infection, while 342 (68.81%) tested positive for malaria parasites. Notably, 15 (3.02%) cases exhibited co-infections with both dengue and malaria parasites, predominantly Plasmodium falciparum. Haemoglobin <12g/dl 100%, thrombocytopenia, haemorrhagic symptoms (26.67%), renal failure (13.33%), and hepatomegaly (46.67%). 93.33% prevalent in co-infections, more with Plasmodium falciparum. Conclusion Co-infections are not uncommon, and failing to identify either condition in cases of concurrent infections can lead to severe complications and potentially disastrous outcomes. Patients from endemic regions must be thoroughly examined, as early diagnosis is critical for effective treatment and can be lifesaving. Recommendation It is essential for all febrile patients exhibiting suggestive symptoms to undergo comprehensive testing for both dengue and malaria infections.